INSURABLE INTEREST UNDER LIFE INSURANCE AND FAMILY TAKAFUL - Abubakar, Yusuf Sani; Zahid, Muhammad Anowar; Markom, Ruzian (Jurnal Syariah, 2015)
This is a doctrinal and comparative research between the traditional law and the Shariah with regard to insurable interest. The paper aims to examine Shariah views regarding individuals that have an insurable interest in the eyes of the traditional law; and also to clarify these persons’ right to insurable interest in the Islamic version of insurance i.e. takaful based on the rights of these individuals upon each other in Shariah. The paper suggests that insurable interest in family takaful could be justified based on inheritance law (al-mirath), bequest (al-wasiyyah), and debt.